Numerical Simulation From Theory to Industry - Andriychuk, Mykhaylo (IntechOpen, 2012)
Numerical Simulation - from Theory to Industry is the edited book containing 25 chapters and divided into four parts. Part 1 is devoted to the background and novel advances of numerical simulation; second part contains simulation applications in the macro- and micro-electrodynamics. Part 3 includes contributions related to fluid dynamics in the natural environment and scientific applications; the last, fourth part is dedicated to simulation in the industrial areas, such as power engineering, metallurgy and building. Recent numerical techniques, as well as software the most accurate and advanced in treating the physical phenomena, are applied in order to explain the investigated processes in terms of numbers. Since the numerical simulation plays a key role in both theoretical and industrial research, this book related to simulation of many physical processes, will be useful for the pure research scientists, applied mathematicians, industrial engineers, and post-graduate students.